POLITIK PEREMPUAN DALAM LEGISLASI NASIONAL DALAM PERSPEKTIF RELASI SOSIAL DAN KEISLAMAN DI KABUPATEN CIREBON - Syamsiyah, Nur; Hardiyana, Andri (Jurnal Harkat : Media Komunikasi Gender, 2025)
Abstract. The formal opening of women’s access to practical politics in Indonesia reflects the government’s commitment to fostering gender-sensitive public policy. However, women’s representation in parliament remains significantly below the expected threshold. In Cirebon Regency, only 13 out of 50 seats (26%) were held by women in the 2014 local election, increasing slightly to 28% in 2019, but declining to 12% in 2024. This study aims to explore women’s political representation in the Cirebon elections through the lens of social relations and Islamic perspectives. This research employs a literature study method, utilizing data from reputable national and international journals, books, media sources, and statistics from the Cirebon Regency Central Statistics Agency. Keywords include: Gender, Women’s Politics, National Legislation, Women’s Electability, Social and Islamic Relations.The findings indicate that the limited representation of women is rooted in two main factors: patriarchal social norms and religious interpretations of leadership. To address these challenges, the study proposes five strategic alternatives: (1) fostering women’s political awareness through direct service actions such as social assistance; (2) promoting political education via religious platforms; (3) transforming patriarchal mindsets through basic leadership training in schools and madrasahs; (4) strengthening female leadership in youth and civic organizations; and (5) embedding religious study groups (jamíyah) as a social subculture to foster public trust in female leadership. These strategies are designed to enhance women’s political electability while harmonizing Islamic values with inclusive democratic practices. Abstrak. Representasi perempuan dalam politik praktis secara formal telah dibuka dan diatur oleh pemerintah untuk mendorong pengambilan kebijakan publik yang sensitif gender. Namun, realitas menunjukkan bahwa keterwakilan perempuan di parlemen masih jauh dari harapan. Di Kabupaten Cirebon, hanya 13 dari 50 kursi (26%) ditempati perempuan pada Pilkada 2014, meningkat menjadi 28% pada 2019, namun turun drastis menjadi 12% pada 2024. Penelitian ini bertujuan menganalisis keterwakilan politik perempuan dalam Pilkada Cirebon melalui tinjauan relasi sosial dan nilai-nilai keislaman. Metode yang digunakan adalah studi literatur dengan sumber dari jurnal ilmiah, buku, media massa, dan data dari Badan Pusat Statistik Kabupaten Cirebon. Kata kunci mencakup: Gender, Politik Perempuan, Legislasi Nasional, Elektabilitas, serta Relasi Sosial dan Keislaman.Hasil penelitian menunjukkan bahwa rendahnya keterwakilan perempuan dipengaruhi oleh dua faktor utama: norma sosial yang mengakar dan pemahaman keislaman tentang kepemimpinan. Untuk mengatasinya, peneliti menawarkan lima alternatif strategis: (1) Membangkitkan kesadaran politik melalui layanan nyata seperti bantuan sosial; (2) Menguatkan pendidikan politik melalui forum keagamaan; (3) Mengubah pola pikir patriarkal lewat pelatihan dasar kepemimpinan di sekolah dan madrasah; (4) Mendorong kepemimpinan perempuan dalam organisasi pemuda dan masyarakat; dan (5) Membumikan pengajian sebagai subkultur sosial untuk membangun kepercayaan publik terhadap kepemimpinan perempuan. Strategi ini bertujuan memperkuat legitimasi dan elektabilitas politik perempuan secara berkelanjutan dalam bingkai nilai-nilai Islam.